Treatment of Extensor Digitorum Brevis Manus Myalgia With Botulinum Toxin. Issue 3 (22nd December 2013) - Wendel, Ian; Cole, Jeffrey
Abstract : Extensor digitorum brevis manus (EDBM) muscles are accessory dorsal hand muscles that are present in 1%‐3% of the population. These muscles are not commonly symptomatic, but they can occasionally cause pain and discomfort and may be misdiagnosed as tenosynovitis or a ganglion cyst. In this case, we describe an appropriate workup of dorsal hand masses and myalgia that are suspected to be related to EDBM muscles. The patient's symptoms were controlled with injections of botulinum toxin into the EDMB muscle belly, which allowed the patient to be relatively pain free for a considerable amount of time and avoid surgery.